De-risking agriculture in Myanmar: Guidebook for building climate resilience among smallholder farmers - Barbon, Wilson John; Khaung, Ye (2023)
In Myanmar, the International Institute of Rural Reconstruction, in partnership with the CGIAR-Climate Change, Agriculture and Food Security (CCAFS), the International Development Research Center Canada (IDRC), the Alliance of Bioversity International and CIAT (The Alliance), and local NGOs, have promoted the climate-smart village (CSV) approach as a community platform to build adaptation capacities of Myanmar farmers since 2017. IIRR, through the four climate-smart villages in Chin State, Southern Shan State, the Central Dry Zone, and the Ayeyarwady delta, promoted climate-smart agriculture practices and technologies, as well as the use of climate information services. This guidebook is an effort to document and guide other non-government agencies aiming to enhance climate resilience in agriculture in Myanmar. It provides both the conceptual basis for the CSV approach and the practical steps and tools to establish CSVs, promote and support climate-smart agriculture, and use climate information services. While this book is not exhaustive, it can provide the basic starting points to initiate, maintain and sustain a community-based climate change adaptation program. It is aimed at program managers and community facilitators planning or implementing climate change programs in agriculture.